{[ promptMessage ]}

Bookmark it

{[ promptMessage ]}

chs1-4review

# chs1-4review - Cumulative Review Solutions Chapters 1 4 2...

This preview shows pages 1–2. Sign up to view the full content.

Chapters 1–4 2. The given function is a polynomial function of degree three. The x- intercept s are –1 and 2. Since –1 is a double root, the graph is tangent to the x -axis at x = –1. The y -intercept is 2. Since the coefficient of the x 3 term is negative, the graph goes from the second quadrant to the fourth quadrant. 4. b. 3 x 3 + 9 x 2 –13 x 2 + 11 x –13 x 2 – 39 x 50 x – 2 50 x 150 – 152 Thus, (3 x 3 – 4 x 2 + 11 x – 2) ( x + 3) = 3 x 2 – 13 x + 50 – x 1 + 52 3 7. Let f ( x ) = x 3 + kx 2 – 4 x + 12. Since x – 3 is a factor of f ( x ), f (3) = 0. Thus, 27 + 9 k – 12 + 12 = 0, and k = –3. 8. Let f ( x ) = x 4 – 2 x 3 + 5 x 2 – 6 x – 8. To determine whether or not x – 2 is a factor of f ( x ), we evaluate f (2). f (2) = 16 – 16 + 20 – 12 – 8 = 0 Since f (2) = 0, x – 2 is a factor of f ( x ) y x 2 0 2 – 1 9. We use the Factor Theorem to determine other factors of the given polynomial. We know that for x p to be a factor, p must be a divisor of 6. Let f ( x ) = x 3 – 2 x 2 – 5 x + 6. Since f (1) = 1 – 2 – 5 + 6 = 0, x – 1 is a factor of f ( x ). Since f (3) = 27 – 18 – 15 + 6 = 0, x – 3 is a factor of f ( x ). Thus, x 3 – 2 x 2 – 5 x + 6 = ( x + 2), ( x – 1), and ( x – 3). 10. d. Let f ( x ) = 5 x 3 + 8 x 2 + 21 x – 10. Since f 2 5 = 0, 5 x – 2 is a factor. By long division, 5 x 3 + 8 x 2 + 21 x – 10 = (5 x – 2)( x 2 + 2 x + 5). The expression x 2 + 2 x + 5 does not factor in x R .

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

{[ snackBarMessage ]}